The Holy Spirit and Higher Education: Renewing the Christian University - Yong, Amos (Baylor University Press, 2023)
Cover Page -- Half Title Page, Title Page, Copyright, Dedication -- Contents -- Preface and Acknowledgments -- 1. Introduction: The Spirit Says Go! Toward a Pentecost-Theology of Christian Higher Education -- Part I: What Difference Has the Holy Spirit Made?: Historical Lessons -- 2. Revisiting Ancient Didaskalia: Patristic Foundations, Medieval Renewal, and Renaissance/Reformation Expansion -- 3. (Re)constructing the University: Modernity and the Quest for Alternative Paradigms -- 4. Reimagining Christian Higher Education: Populism and the Transformation of Folk Culture in the Twentieth Century -- Part II: What Difference Can the Holy Spirit Make?: Constructive Reenvisioning -- 5. Renewing the Mind: Scholarship and the Pneumatological Imagination -- 6. Reordering the Heart: Teaching, Learning, and the School of the Holy Spirit -- 7. Revitalizing the Hands: The Spirit's Mission in and through Christian Higher Education -- 8. Conclusion: The Spirit Says Come! Renewing the Christian University -- Index of Subjects and Authors -- Index of Scripture.